PENGARUH TINGKAT FEAR OF MISSING OUT (FOMO) DAN TINGKAT SOCIAL OVERLOAD TERHADAP INTENSI PENGHENTIAN PENGGUNAAN INSTAGRAM - Rania Rizki Zulkarnain; S. Rouli Manalu (Interaksi Online, 2023)
The proliferation of social media platforms has provided researchers with ample opportunities to explore the implications of these platforms' positive and negative use. Focusing on the latter, this research has highlighted the implications of the fear of missing out (FoMO) and social overload as two from many aspects of social media inappropriate use. Previous studies on this aspect mainly focuses on Facebook and Weibo as social media in used, meanwhile based on a survey conducted by Royal Society for Public Health in England at 2017 shows that among five social media platforms commonly used by people, Instagram placed number one in being the most negative social media that impact young people's mental health. This paper analyzes whether fear of missing out and social overload has effects on user intention to leave or quit using social media, specifically Instagram. This study uses previous research as a reference for reducing the hypothesis. In determining the sample, this study used a non-probability sampling technique and took a total of 200 samples. the criteria of this research sample are students of Diponegoro University Communication Sciences who enroll from year 2018 to 2022, and have an Instagram account. Tests were carried using simple linear regression analysis. Results shows that fear of missing out has an influence on discontinuance use of Instagram with significance value of 0,000  0,01 which means highly significant, and R Square of 0,441 or an influence value of 44,1 percent. Furthermore, social overload also has an influence on discontinuance use of Instagram with significance value of 0,000  0,01 which means highly significant, and R Square of 0,485 or an influence value of 48,5 percent.